Searching for a 'principle of humanity' in international humanitarian law - Larsen, Kjetil Mujezinovic; Cooper, Camilla Guldahl; Nystuen, Gro (Cambridge University Press, 2013)
The legal norms of international humanitarian law (IHL) are the product of a compromise between humanitarian considerations and the demands of military necessity. This book examines whether a particular 'Nordic Perspective' can be identified, owing to those states' involvement in armed conflicts outside their own territories in the post-Second World War era.